ANALISIS PENGARUH LIKUIDITAS, LEVERAGE DAN AKTIVITAS PERUSAHAAN TERHADAP PROFITABILITAS PADA SUB SEKTOR PERDAGANGAN BESAR BARANG PRODUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11108090, Rahmat Illahi (Jurnal Manajemen Update, 2013)
This research entitles The Influence analysis of Liquidity, Leverage and Activity to Profitability of Sub Sector Activity on Goods Wholesale Production in Indonesia Stock Exchange (Bursa Efek Indonesia/BEI). The purpose of this research is to determine whether there is influence of liquidity ratio, leverage ratio and Ratio of Activity to Return on Assets of Goods Wholesale Production Companies at the Indonesia Stock Exchange from the period 2006-2011. The total of sample are 10 Goods Wholesale Production Companies at the Indonesia Stock Exchange. The collecting data method uses documentation study. Method of data analysis uses descriptive analysis and multiple linear regression analysis. The result of this research shows that current ratio, debt to equity ratio, total assets turn over and firm size variables influence simultaneously to Return on Assets of Goods Wholesale Production Companies at the Indonesia Stock Exchange. The result of the partial, only total assets turn over and firm size variables influence significantly and positive to Return on Assets of Goods Wholesale Production Companies at the Indonesia Stock Exchange. The amount of determinant coefficient (R2) 0,649 or 64,9% means the ability of explaining the influence current ratio, debt to equity ratio, total assets turn over and firm size variables to return on assets while the remaining is influenced by others independent variables which are not examined in this research. Keywords : Liquidity (current ratio), Leverage (debt to equity ratio), Activity (total assets turn over), Firm size (log natural of total assets) and Profitability (return on assets)